GLOBALIZATION AND INEQUALITIES IN DEVELOPED ECONOMIES: KUZNETS WAS NOT RIGHT - Berumen, Sergio A. (2015)
In this paper we first review the concepts of Globalization and Inequality, paying special attention to the conclusions reached previously by Simon Kuznets and his followers. Later we carry on with an international comparison between Sweden and the United States for the period 1913-2012. We depict the evolution in inequality levels for both countries, based in two main indicators: the Gini Index and the top 1% income share. Our findings point out that inequality has strongly risen in the United States whilst Sweden’s level of inequality is not far from the one presented immediately after the World War II. These results may indicate Sweden’s higher ability to deal with the globalization aftermaths.